Peningkatan Hasil Belajar Menulis Naratif melalui Gambar Berseri Berbantuan Multimedia - Ida Ayu Putu Kerti (Universitas Muhammadiyah Magelang, 2020)
The purpose of this study was to improve the results of narrative writing learning through series of picture teaching with multimedia aids. The subjects were grade VIIIA students of SMP Negeri 4 Sukasada in academic year 2017/2018 as many as 26 students. The object was the students’ narrative writing learning outcomes. It used classroom action research (CAR) which covered for 2 (two) cycles, including planning, action, observation/ evaluation, and reflection in each cycle. The data collection was conducted through classroom observation and test. Data were analyzed descriptively. The results of the study in narrative writing showed there was an increase in the average of learning outcomes from 72,5 in cycle I to 78,7 in cycle II, students’ learning completeness from 62% in cycle-1 to be 88% cycle-2, and learning absorpion power from cycle-1 72,5% to be 78,7% in cycle-2.